PENGARUH PENGGUNAAN MODEL PROBLEM BASED LEARNING (PBL) TERHADAP HASIL BELAJAR SISWA DALAM PEMBELAJARAN IPS DI KELAS V SD - Alfianiawati, Tia; Desyandri, Desyandri; Nasrul, Nasrul (Universitas Negeri Padang, 2018)
The aim of the research is to describe the effects of using the Problem-Based Learning Model (PBL) toward students’ learning outcomes in learning Social Science Subjects. The research was True Experimental Design in form of Pretest - Posttest Control Group Design. The subjects of the research were all of the students at grade 5th of SD Negeri 29 Dadok Tunggul Hitam. The Sampling technique used in this research is the simple random sampling. The research sample were 29 students at grade 5th of class VA and class VB in SD Negeri 29 Dadok Tunggul Hitam. Data were analyzed by using calculation with the t-test. It was found that tcalculation < ttable as t2,00324 < t2,994 with α = 0,05. Thus, it is concluded thatt there is a significant effect of using the Problem Based Learning Model. It has improved the students’ learning outcomes in learning Social Science Subjects at grade 5th of Elementary School.